Climate change : (Gale, Cengage Learning, 2008)
Designed to explain “the complexity of the 2007 Intergovernmental Panel on Climate Change (IPCC) reports to younger students,” the volumes contain 250 articles contributed by various science writers and academics in geology, law, and environmental science. The articles are organized alphabetically into two volumes, the first covering Abrupt climate change through Gulf Stream and the second covering Halocarbons through World Meteorological Organization. Article length ranges from two to seven pages, and each article has a standard format consisting of “Introduction”; “Historical Background and Scientific Foundations”; “Impacts and Issues”; a bibliography that may include books, periodicals, and Web sites; a “Words To Know” sidebar; and extensive cross-references.